Proteolitic Activity of Marine Strain Bacillus sp. 051 - Gudzenko, O.V.; Ivanytsia, V.O.; Varbanets, L.D.; Гудзенко, О.В.; Іваниця, В.О.; Варбанець, Л.Д. (PH "Akademperiodyka" of the NAS of Ukraine, 2023)
The main interest in the study of marine microorganisms is due to their ability to produce a wide range of unique enzymes, including peptidases with different specificities. In recent years, interest has increased in peptidases that are able to cleave elastin as a specific substrate. Streptomyces fradiae and Bacillus thermoproteolyticus elastases are among the most potent elastolytic proteinases discovered to date because they are 4-8-fold more effective than pancreatic elastases. The disadvantages of these producers include the fact that most of them are pathogenic for humans, and the elastase enzyme secreted from them is directly involved in the initiation of the pathogenetic process. All this significantly limits the scope of their practical application. Therefore, the search for new, more effective, safe for humans’ producers continues to be an urgent question, taking into account the fact that there are no highly active elastase producers in Ukraine. Previously we found elastase activity in only 4 of the 10 studied isolates of bacteria from the Black Sea. Since among them, the elastase activity of the Bacillus sp. 051 was the highest, the aim of this work was to study the physicochemical properties and substrate specificity of the enzyme. Methods. We used methods of determining proteolytic (caseinolytic, elastolytic, fibrinolytic, fibrinogenolytic) activity. Protein concentration was determined by the Lowry method. The study of the effect of temperature on the enzymatic activity was carried out in the range from 4 to 70 °C and pH values from 2.0 to 12.0, created using 0.01 M phosphate-citrate buffer. Results. It has been shown that the growing temperature of 12°C is the most optimal for biosynthesis of enzyme by the culture of Bacillus sp. 051. The complex enzyme preparation capable of hydrolyzing elastin, casein and fibrinogen. The enzyme showed maximum activity in relation to elastin (3.65 U/mg). The optimum pH of the enzyme action is 8.0, the thermal optimum is 40°C. The rate of casein hydrolysis compared to elastin was 2.7 times lower and amounted to 1.35 U/mg. The complex enzyme preparation also hydrolyzed fibrinogen (1.16 U/mg). Conclusions. According to its physicochemical and catalytic properties, the representative of the Black Sea, Bacillus sp. 051 is promising for further research as an enzyme producer with elastolytic activity.